Bridging urban discontent - Du Plessis, Devin (School of Architecture, Planning and Geomatics, 2018)
There exists an incoherence in many contemporary cities between built architectural, urban fabric and the main transport arteries that feed the city. This incoherence leads to dangerous and disused space in the city which leads to disconnected parts owing to the untraversable nature of these left-over spaces. While there are large engineering solutions to such problems, this project seeks architectural solutions. Contemporary tools can be used to analyse and handle the problem; leading to a healthier city with happier people. The current tools at an architect's disposal allow him/ her to respond to a variety of contextual geometries of varying complexity. These tools present themselves in the form of algorithm based software. The concepts of the project seek to create flows through the city by making spaces that show movement and interrelation and encourage constant activation. To do this a specific city has been used as a case study and a particular site selected for a hypothetical architectural project to be designed. This design grapples with the aforementioned issues and solves the challenges firstly by trying to understand why the dead spaces exist and accepting that the transport elements which led to the disconnect cannot necessarily change. This is a positive project seeking to uplift the city.